2017
DOI: 10.1039/c7nr01516j
|View full text |Cite
|
Sign up to set email alerts
|

Radio frequency negative permittivity in random carbon nanotubes/alumina nanocomposites

Abstract: While metal is the most common conductive constituent element in the preparation of metamaterials, one-dimensional conductive carbon nanotubes (CNTs) provide alternative building blocks. Here alumina (AlO) nanocomposites with multi-walled carbon nanotubes (MWCNTs) uniformly dispersed in the alumina matrix were prepared by hot-pressing sintering. As the MWCNT content increased, the formed conductive MWCNT networks led to the occurrence of the percolation phenomenon and a change of the conductive mechanism. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 166 publications
(90 citation statements)
references
References 72 publications
4
86
0
Order By: Relevance
“…In fact, ε'' represents energy loss of the media in electric field, and it was typically considered as the combined contribution of conduction loss ( ′′ c ) and polarization loss ( ′′ p ), which could be expressed as following. 20,48 The first half the equation represents ′′ c , which is closely related to the current conductivity within the material, and the second represents ′′ p that is dependent on dielectric relaxation of the material. ε'' spectra in Figure 4C show that ε'' of ceramics with high TiN content declined almost in inverse proportion with frequency, and this suggested that ′′ c issued from the electric currents among TiN clusters played the primary role in total energy loss.…”
Section: Ac Conductivity and Electric Percolationmentioning
confidence: 99%
“…In fact, ε'' represents energy loss of the media in electric field, and it was typically considered as the combined contribution of conduction loss ( ′′ c ) and polarization loss ( ′′ p ), which could be expressed as following. 20,48 The first half the equation represents ′′ c , which is closely related to the current conductivity within the material, and the second represents ′′ p that is dependent on dielectric relaxation of the material. ε'' spectra in Figure 4C show that ε'' of ceramics with high TiN content declined almost in inverse proportion with frequency, and this suggested that ′′ c issued from the electric currents among TiN clusters played the primary role in total energy loss.…”
Section: Ac Conductivity and Electric Percolationmentioning
confidence: 99%
“…Fan et al16–18 have incorporated metal or alloy particles into ceramics and initially realized negative permittivity based on the plasma oscillation of electrons. Afterward, the negative permittivity was also attained in carbon nanotubes/alumina nanocomposites,19 graphene/alumina composites20 and titanium nitride/alumina composites,21 and so forth. In recent years, the polymer‐based metacomposites have also aroused considerable interest owing to their good processability and low manufacturing cost.…”
Section: Introductionmentioning
confidence: 96%
“…To improve the performance, a common method is the addition of appropriate nanofillers into polymer matrix . Compared with neat TPU, the addition of carbon‐based nanoparticles can improve the mechanical properties and thermal stability of the composites, thereby enhancing the solid particle erosion resistance of the composite.…”
Section: Introductionmentioning
confidence: 99%